2011
DOI: 10.3844/ajavsp.2011.25.30
|View full text |Cite
|
Sign up to set email alerts
|

Extrusion of Peas (Pisum sativum L.): Effects on the Apparent Metabolisable Energy and Ileal Nutrient Digestibility of Broilers

Abstract: Problem statement:The potential feeding values of grain legumes, such as peas (Pisum sativum), are limited because of the presence of anti-nutritional factors. In particular, protease inhibitors are of interest, but these can be readily destroyed by thermal treatments. In the present study, the influence of extrusion on the chemical composition and nutritive value of peas was evaluated. Approach: Two extrudates were produced by extruding the peas at two moisture levels (19 and 22%) and one temperature (140°C)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
2
9
1
Order By: Relevance
“…Nevertheless, total period FI was higher (p>0.05) in the control treatment (37,900 Kg) than in the T2, T3 and T4 (37,838, 37,821, and 37,736 Kg, respectively). The findings of the present study is in conformity with the findings of the previous research works [26,27], but at the same time they were not in conformity with the findings of the researchers who witnessed increased intake of EFFSB [16]. This might be due to an underestimation of the energy content of the beans used, and was probably because the energy value available to the bird because of rolling and extrusion, coupled with pelleting of the diets, was underestimated.…”
Section: Feed Intakesupporting
confidence: 67%
“…Nevertheless, total period FI was higher (p>0.05) in the control treatment (37,900 Kg) than in the T2, T3 and T4 (37,838, 37,821, and 37,736 Kg, respectively). The findings of the present study is in conformity with the findings of the previous research works [26,27], but at the same time they were not in conformity with the findings of the researchers who witnessed increased intake of EFFSB [16]. This might be due to an underestimation of the energy content of the beans used, and was probably because the energy value available to the bird because of rolling and extrusion, coupled with pelleting of the diets, was underestimated.…”
Section: Feed Intakesupporting
confidence: 67%
“…According to van der Poel (1992), the degree of trypsin inhibitor inactivation after extrusion depends on the processing conditions (temperature and moisture content) and the cultivar used, being more effective under conditions of higher moisture and temperature and in round-seeded than in wrinkle-seeded peas. The efficacy of extrusion in lowering trypsin inhibitor activity in peas shown in literature ranges from 17% (Nalle et al, 2011) through 55% (Diaz et al, 2006), 87% (Leontowicz et al, 2001), to 95% (Alonso et al, 2000). The last authors reported that also 65% of chymotrypsin inhibitors were inactivated and 98% of the haemagglutinating activity of peas disappears after the extrusion cooking applied in the study.…”
Section: Discussionmentioning
confidence: 87%
“…Extrusion has been reported to have positive effects on in vitro protein and starch digestibility and on the nutritional value of peas in rats (Alonso et al, 2000;Leontowicz et al, 2001). In chickens, extrusion of peas increased ileal starch digestibility, but had no effect on apparent ileal protein digestibility or apparent metabolizable energy (Nalle et al, 2011). Information on the effect of pea extrusion and pea level in broiler diets on the intestinal epithelium and activity of GIT microbiota are scarce.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations